2005
DOI: 10.1007/s11064-004-9682-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased 5-HT1A Receptor Gene Expression and 5-HT1A Receptor Protein in the Cerebral Cortex and Brain Stem during Pancreatic Regeneration in Rats

Abstract: The present study was to investigate the role of central 5-HT and 5-HT(1A) receptor binding and gene expression in a rat model of pancreatic regeneration using 60% pancreatectomy. The pancreatic regeneration was evaluated by 5-HT content and 5-HT(1A) receptor gene expression in the cerebral cortex (CC) and brain stem (BS) of sham operated, 72 h and 7 days pancreatectomised rats. 5-HT content significantly increased in the CC (P < 0.01) and BS (P < 0.05) of 72 h pancreatectomised rats. Sympathetic activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The role of hypothalamic GABAergic neurotransmission in regulating sympathetic system during liver regeneration has also been reported from our laboratory [17]. Also, the decreased 5-HT 1A and 5-HT 2C receptor binding in the cerebral cortex and brain stem was reported which is stimulatory to insulin release mediated through the sympathetic system in pancreatic regeneration [18,19]. Though many reports are there implicating the brain control of pancreatic function how the central a 1 -adrenergic receptors respond to pancreatic regeneration is not well studied.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The role of hypothalamic GABAergic neurotransmission in regulating sympathetic system during liver regeneration has also been reported from our laboratory [17]. Also, the decreased 5-HT 1A and 5-HT 2C receptor binding in the cerebral cortex and brain stem was reported which is stimulatory to insulin release mediated through the sympathetic system in pancreatic regeneration [18,19]. Though many reports are there implicating the brain control of pancreatic function how the central a 1 -adrenergic receptors respond to pancreatic regeneration is not well studied.…”
Section: Introductionsupporting
confidence: 62%
“…Insulin can stimulate b-cell replication directly possibly through a receptor for multiplication stimulating activity or another insulin like growth factor [32]. Tritiated thymidine incorporation studies from our laboratory [18] and previous reports showed that the DNA synthesis in pancreatic islets was maximum at 72 h after pancreatectomy i.e. during active pancreatic regeneration [20,33].…”
Section: Discussionmentioning
confidence: 92%
“…Tritiated thymidine incorporation studies from our laboratory [21] and previous reports showed that the DNA synthesis in pancreatic islet was maximum at 72 It after pancreatectomy i.e. during active pancreatic regeneration.…”
Section: Discussionmentioning
confidence: 53%
“…The increased sympathetic stimulation leads to hypertension in pyridoxine deficient rats [5], which in turn lead to diabetes [8]. The decreased binding of the 5-HT 1A and 5-HT 2C receptors in the cerebral cortex and brain stem during pancreatic regeneration suggests the stimulatory role of insulin secretion mediated through the sympathetic system [11,12]. The muscarinic M1 receptor in the brain stem decreased at 72 h after partial pancreatectomy and M3 receptors increased at the time of pancreatic regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal stimulation is involved in the sensitization of islets to physiological elevated levels of glucose concentrations [4]. Earlier studies from our laboratory have established the central neurotransmitter receptor subtypes functional regulation during pancreatic regeneration, diabetes and cell proliferation [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%